Macromol. Symp. 386. Issue 1 (14th August 2019) - Unknown
Abstract : Cover: This issue of Macromolecular Symposia contains selected papers presented at the 12 th International IUPAC Conference on Polymer‐Solvent Complexes and Intercalates which took place in Grenoble, France, on September 4–7, 2018 under the name POLYSOLVAT‐12. The cover picture shows the conference logo against the background of the Grenoble area, featuring the European Photo & Neutron Campus that hosts Institut Laue‐Langevin, France. © D. Morel / ILL.